Corrigendum to "Phase-field theory of grain growth in the presence of mobile second-phase particles" [Acta Mater. 58 (2010) 272-281] (DOI:10.1016/j.actamat.2009.09.001) - Vedantam, S. (2014)
10.1016/j.actamat.2009.12.008